Differences in the Impact of Heart Rate Variability on the Surgical Approach in Patients With Early Cervical Cancer: Laparoscopic versus Open Surgery - Liu, Jian; Wang, Jingfeng; Deng, Zhaoya; Liu, Shiqi; Li, Guangqiao; Sun, Yilin; Gao, Longfei; Li, Chenghui; Shi, Bo (Frontiers in Oncology, 2022)
Background Evidence suggests that the risk of recurrence and death in patients with early cervical cancer (ECC) undergoing minimally invasive surgery is significantly higher than that in patients undergoing open surgery. However, the mechanisms underlying such a difference remain unclear. Heart rate variability (HRV) represents autonomic nerve activity, which is related to tumorgenesis and can be used as a prognostic indicator for various cancers. The main purpose of this study was to explore the difference in the effects of laparoscopic and open surgery on HRV in ECC patients. Methods A total of 66 ECC (FIGO IA1 with lymphovascular space invasion -IIA2) patients undergoing radical hysterectomy for the first time (86% open group vs. 14% laparoscopic group) were included. A single-lead micro-ECG recorder was used to collect 5 min electrocardiograms 1 day before the operation and 3 days after the operation, and then HRV time domain and frequency domain indices were analyzed, including mean heart rate (MeanHR), maximum heart rate (MaxHR), minimum heart rate (MinHR), the standard deviation of all normal-to-normal intervals (SDNN), the root mean square of successive interval differences (RMSSD), very low-frequency power (VLF), low-frequency power (LF), high-frequency power (HF), total power (TP), and the ratio of LF to HF (LF/HF). Results Heart rate (i.e., MeanHR, MaxHR, and MinHR) were significantly higher, and HRV (i.e., SDNN, RMSSD, LF, HF, and TP) were significantly lower after the operation than before the operation in both the laparoscopic and open groups (P < 0.05). The postoperative reduction in RMSSD and HF was significantly higher in the laparoscopic group than in the open group (P < 0.05). Conclusions These data suggest that radical hysterectomy can lead to increased heart rate and decreased HRV in patients with ECC, which can negatively affect cardiac autonomic regulation. Compared with open surgery, laparoscopic surgery has a greater negative impact on the HRV of ECC patients.